Artificial Intelligence as a Basic and Centre for Integrated Digital Bureaucracy - Hajar, Siti (Jurnal Penelitian Pendidikan IPA, 2023)
Digital technology, whose deepest spirit is artificial intelligence, seems to be man's last love. It was created to serve man so that his stutus glory is perfected by the results of his mind, and the mind is a gift from God of the universe that is complete. The purpose of this research is to describe the use of artificial intelligence technology to support the bureaucratic system in our country. This research is descriptive, with the methodological basis being qualitative research. The research method is a literature study, with the main sources being writings sourced from scientific journals, mass media publications and other relevant sources. The writings are elaborately narrated with the guidance of relevant theories. The results of the study found several factors in the implementation of this digital bureaucracy, namely (1) Availability of an integrated system, (2) Placement of human resources according to their fields and capabilities, (3) Sustainability of the program and (4) Periodic improvement of infrastructure (software and hardware) as needed.